World watch geography skills book 2 A geography skills book for grade 7 - Moorcroft, Christine (Karachi: Oxford university press, 2024)
It builds on students' experience from earlier work in geography by introducing higher-level geographical skills. It presents a student-friendly approach with a conversational tone to engage their interest. Reinforces mapping skills through activities to plan routes, interpret symbols and legends, and solve map based problems.
Keywords: Oxford - geography textbook